2015
DOI: 10.1007/s00251-015-0876-8
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 and leptin genes polymorphisms and their levels in relation to recurrent pregnancy loss in Egyptian females

Abstract: Recurrent pregnancy loss (RPL) is a common problem during early gestation. The aim of our study was to investigate the association of IL-17 F( rs763780), IL-17 A (rs2275913), and leptin (2548 G/A) gene polymorphisms with RPL in obese and lean Egyptian females, and to find out whether these gene polymorphisms affect the women’s serum levels. One hundred and twenty patients with RPL and 120 fertile volunteers with no history of pregnancy loss were genotyped for leptin (2548 G/A), IL-17 A (rs2275913), and IL-17 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 41 publications
3
19
3
1
Order By: Relevance
“…These findings are in line with a previous demonstration of the absence of a clinically meaningful correlation between leptin ‐2548 (G/A) and RPL . In contrast, our findings contrast with those of three other studies in which (i) the variant G allele of the adiponectin 276 polymorphism was associated with a 1.36‐fold greater risk in Indian women with RPL, and (ii) the frequency of A allele gene of leptin ‐2548 polymorphism in Egyptian and Chinese women with RPL was significantly higher than in control groups . There are several possible explanations for these discrepancies.…”
Section: Discussionsupporting
confidence: 81%
“…These findings are in line with a previous demonstration of the absence of a clinically meaningful correlation between leptin ‐2548 (G/A) and RPL . In contrast, our findings contrast with those of three other studies in which (i) the variant G allele of the adiponectin 276 polymorphism was associated with a 1.36‐fold greater risk in Indian women with RPL, and (ii) the frequency of A allele gene of leptin ‐2548 polymorphism in Egyptian and Chinese women with RPL was significantly higher than in control groups . There are several possible explanations for these discrepancies.…”
Section: Discussionsupporting
confidence: 81%
“…It should be noted, however, that this study conducted with Colombian patients shows that the IL17A rs8193036 SNV is probably in linkage disequilibrium with some causative variant that modulates IL17A production (38). This investigation also found no association between the IL17A rs7747909 G>A 3' UTR SNV and Chagas cardiopathy and between two other IL17A promoter SNVs (rs4711998 and rs3819024) or IL17A rs2275913 and heart disease, in a context where the latter A allele is associated with increased IL17 A levels (40,41). A previous study, in turn, reported association of the IL17A rs2275913 G>A (promoter SNV) A allele and AA genotype with chronic cardiomyopathy in Brazil (42).…”
Section: Introductioncontrasting
confidence: 67%
“…Serum leptin concentration was found elevated in women with recurrent miscarriage in comparison to control group . However, in women who subsequently miscarried, it was found that at weeks 5–6 and 7–8 plasma leptin concentrations are also lower than women who subsequently had a term birth .…”
Section: Leptin and Pathologies Associated With Pregnancymentioning
confidence: 73%
“…On the other hand, Chin et al [105] did not find a correlation between this polymorphism and recurrent miscarriage. However, other studies have reported that these genetic variants are associated with pregnancy recurrent loss (Table 1) [100,106].…”
Section: Recurrent Miscarriagementioning
confidence: 99%